Business Management of MSMEs in Manado City its Problem and Development Strategy - Agus Supandi Soegoto; Frederik G. Worang (AIBPM Publisher, 2018)
MSMEs business in Manado city has its own role in the economy both in the Manado city, and in the province of North Sulawesi. Nationally, it can also be seen that MSMEs businesses have a strategic role in strengthening the national economy. MSMEs have advantages, because MSME business actors move in various business fields and directly touch the interests of the community, especially the middle and lower economic groups when viewed from the aspect of the purchasing power of the people as consumers. But when viewed from the aspect of business development and sustainability, MSMEs seem to develop slowly, business sustainability is still in doubt so it needs to get serious attention from the regional government and especially related institutions, namely the Cooperatives service (Dinas Koperasi), Banking and Higher Education. The purpose of this study was to (1) find out the profile and problems of MSMEs in Manado City, (2) Analyze MSMEs business management and development strategies (3) provide solutions to problems and development of MSMEs businesses. Management of operations and capability of the MSMEs business in the Manado city, still has to get serious and very strategic attention, so it must be considered both by the local government, and related parties, considering the average MSMEs in the Manado city the management of its business management is still simple, locally oriented, and many SMEs have not have a business development plan, with the reason that they are still oriented to survive competition and limited business capital. Keywords: strategy, problems, management, business development of MSMEs